Inflammasomes: An Emerging Mechanism Translating Environmental Toxicant Exposure Into Neuroinflammation in Parkinson’s Disease - Anderson, Faith L (Toxicol Sci, 2018)
Evidence indicates that complex gene-environment interactions underlie the incidence and progression of Parkinson’s disease (PD). Neuroinflammation is a well-characterized feature of PD widely believed to exacerbate the neurodegenerative process. Environmental toxicants associated with PD, such as pesticides and heavy metals, can cause cellular damage and stress potentially triggering an inflammatory response. Toxicant exposure can cause stress and damage to cells by impairing mitochondrial function, deregulating lysosomal function, and enhancing the spread of misfolded proteins. These stress-associated mechanisms produce sterile triggers such as reactive oxygen species (ROS) along with a variety of proteinaceous insults that are well documented in PD. These associations provide a compelling rationale for analysis of sterile inflammatory mechanisms that may link environmental exposure to neuroinflammation and PD progression. Intracellular inflammasomes are cytosolic assemblies of proteins that contain pattern recognition receptors, and a growing body of evidence implicates the association between inflammasome activation and neurodegenerative disease. Characterization of how inflammasomes may function in PD is a high priority because the majority of PD cases are sporadic, supporting the widely held belief that environmental exposure is a major factor in disease initiation and progression. Inflammasomes may represent a common mechanism that helps to explain the strong association between exposure and PD by mechanistically linking environmental toxicant-driven cellular stress with neuroinflammation and ultimately cell death.